Making a statement - Ze, Cyprien Essong (Technical Centre for Agricultural and Rural Cooperation, 2002)
It's thanks to his travels that he finally meets up with Spore, which he uses a lot on his farm. We first met on a Roman hillside in Italy, where he was organising farmers' encounters during the World Food Summit. A month later, on another hill, in...